Microcirculatory effects of L-arginine during acute anaerobic exercise in healthy men: A pilot study - Andrius Pranskunas; Zivile Pranskuniene; Jurga Bernatoniene; Egle Vaitkaitiene; Marius Brazaitis (Elsevier, 2015)
Background/Objective: We hypothesized that L-arginine supplementation increases sublingual capillary perfusion during acute anaerobic exercise. Methods: In a double-blind randomized study, 20 healthy men were randomly assigned to an L-arginine group or a placebo group. Both groups performed a standard 60-second duration BOSCO jumping test. Before the exercise, immediately after, and 30 minutes after exercise, systemic hemodynamic parameters were recorded. Sublingual evaluation of microcirculation using sidestream dark field (SDF) videomicroscopy was also carried out. Results: There were no differences in mean arterial blood pressure and cardiac output between the placebo and L-arginine groups immediately after exercise and at 30 minutes after exercise. Both groups had no changes in the microvascular flow index and proportion of perfused vessels of small vessels over the testing period. We observed significantly higher functional capillary density [14.1 (12.5 - 16.0) vs. 11.7 (10.9 - 12.9) 1/mm, p = 0.021] and total vessel density of small vessels [27.8 (24.4 - 29.2) vs. 23.0 (21.6 - 24.2) mm/mm2, p = 0.041] in the L-arginine group compared with the placebo group immediately after exercise, but after 30 minutes these differences had disappeared. Conclusion: Our findings show that supplementation with L-arginine may cause additional effects on the acute anaerobic exercise-induced transient increase in capillary density in the sublingual mucosa of untrained men.